Immobilization of Amorphous NiB Nanoparticles on Mesoporous Supports: Superior Catalysis for Controllably Hydrolyzing NaBH4 to Release H2 - Quanxing Liu; Jun Zhang; Xigang Du; Gang Mi; Yana Dong (Journal of Chemistry)
Taking Ni(CH3COO)2 and NaBH4 as the Ni and B sources and selecting three kinds of mesoporous materials (carbon nanotube (CNTs), activated carbon (AC), and silica (SiO2)) as supports, the liquid-phase reduction-in situ deposition tactics was employed to fabricate the amorphous alloy NiB and its corresponding supported catalysts (NiB/CNTs, NiB/AC, and NiB/SiO2) with assistance of a suitable stabilizer and ultrasonic treatment. The X-ray powder diffraction, transmission electron microscopy, and inductively coupled plasma atomic emission spectrometry were used to characterize the morphology and phase composition of the products. The catalytic activity of the four products for the hydrolytic hydrogen release in NaBH4 solution under different conditions was minutely investigated. The research results indicate that the as-fabricated products belong to amorphous alloy nanoparticles with the single phase and higher purity. The satisfactory dispersion and stronger interaction between NiB and CNTs give NiB/CNTs the best thermal stability. All the four catalysts hold satisfactory catalysis, but their catalytic abilities are obviously discrepant, in the following order: NiB/CNTs > NiB/SiO2 > NiB > NiB/AC. The mean reaction turnover frequency of the NiB/CNTs catalyst at both 318 K and 298 K separately comes up to 28206 ml(H2)·min−1·g−1(NiB) and 13424 ml(H2)·min−1·g−1(NiB), with an apparent activation energy of 47.37 kJ·mol−1. The proposed synthetic strategy could be extended to the fabrication of other similar amorphous alloy catalysts, expected for extensive application prospect.